Comparison of Safety and Effectiveness of Bivalirudin Between Diabetic and Nondiabetic Acute Coronary Syndrome Patients Undergoing Percutaneous Coronary Intervention (Journal of Dhaka Medical College, 2023)
Background: Recurrent thrombotic events remain significantly high in spite of the currently recommended dual antiplatelet (DAPT) and conventional antithrombotic heparin (± GPI/ glycoprotein IIb/IIIa inhibitor) in diabetic ACS patients after PCI compared with non-diabetic even this drug eluting stent (DES) era. Therefore, more potent antithrombotic therapies are warranted for this group of high-risk patients.Comparison of safety and efficacy of newer anticoagulant bivalirudin between diabetic and non-diabetic ACS patients undergoing PCI using bivalirudin versus heparin (± GPI) is less well defined in Bangladeshi population.Objective: To determine and compare the incidence of 30-day major adverse cardiac events (MACEs), stent thrombosis and hemorrhagic complications between diabetic and non-diabetic ACS patients undergoing PCI. Impact of antithrombotic strategy (bivalirudin vs. heparin ± GPI) on the 30- day post PCI clinical outcome was also evaluated and compared between diabetic and non-diabetic subgroup.Methods: In this randomized controlled study, 500 ACS patients aged 18-75 years (200diabetic and 300 non-diabetics) who underwent PCI from November 2018 to October 2019 at the department of cardiology, BSMMU, were randomly assigned, in an open-label fashion to treatment with bivalirudin alone, heparin alone, or heparin plus eptifibatide (GPI) in a 1:1:1 ratio. Among them, 200 patients received Bivalirudin with a loading dose of 0.75 mg/kg, followed by an infusion of 1.75 mg/kg/h for up to 4 hours, 153 patients received UFH with a bolus of 70-100 U/kg (targeted ACT: 200-250 s) and 147 patients got heparin plus eptifibatide as 60 IU/kg heparin along with 180 μg/kg eptifibatide i.v. boluses, followed by a 2 μg /kg /min eptifibatide infusion for 18 hr consistent with current guidelines.Other pre- and post-procedural medications got under current guidelines. Both diabetic and non-diabetic subjects were subdivided into bivalirudin and control group (heparin ± GPI). In diabetic cohort, 100 patients were in bivalirudin and 100 patients were in control group. Among non -diabetic patients, 100 were in bivalirudin and 200 were in control group. The outcome measures were 30-day hemorrhagic complications, stent thrombosis, and MACCEs [death, MI, target lesion revascularization (TLR), and stroke] according to diabetic status. The diabetic and non-diabetic subgroup was also analyzed for the same outcome measure according to antithrombotic strategy. Peri and post PCI clinical follow-up comprised checking office visits and telephone contacts.Results: According to diabetic status, net adverse clinical events (NACEs) were significantly higher in diabetic in comparison to non-diabetic (diabetic vs. non-diabetic, 15% vs. 7.6 %, P=0.008) and was associated with higher incidence of MACCEs (10.5% vs. 4.0%, P=0.004), cardiac death (4 % vs. 1 %, P=0.02) and BARC 2,3,5 grade bleeding events (9% vs. 4 %, P=0.02). In diabetic cohort, incidence of 30-day NACEs was significantly lower in bivalirudin than control group(bivalirudin vs. UFH ± GPI, 6 % vs. 24 %, P=0.004) and was associated with lower incidence of MACCEs (2% vs. 8.5%, P=0.03) and bleeding events (3 % vs. 15 %, P=0.003) whereas incidence of stent thrombosis (2 % vs. 3%, P =0.651) was comparable between the bivalirudin and control groups. There was a significant advantage in favor of bivalirudin treatment among insulin-treated patients with regard to cardiac death at 30-day (bivalirudin vs. control group, 0% vs. 16.6%, p = 0.03) compared with non-insulin treat diabetic patients. However, subgroup analysis of the nondiabetic patients showed that there was no significant difference in the incidence of 30-Day NACEs (4% vs. 9.5%, P=0.09) according anticoagulant status.Multivariate analysis showed that bivalirudin (HR: 0. 202, 95% CI: 0.078 – 0.519, P=0.009) was independent protective factor of 30-day NACEs for diabetic patients.Conclusion: Bivalirudin monotherapy is safer and more efficacious for diabetic ACS patients compared with non-diabetic ACS patients undergoing PCI.J Dhaka Med Coll. 2022; 31(1) : 126-136